2007
DOI: 10.1016/j.ijpara.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing of the tick protective antigens, Bm86, Bm91 and subolesin, in the one-host tick Boophilus microplus by RNA interference

Abstract: The use of RNA interference (RNAi) to assess gene function has been demonstrated in several three-host tick species but adaptation of RNAi to the one-host tick, Boophilus microplus, has not been reported. We evaluated the application of RNAi in B. microplus and the effect of gene silencing on three tick-protective antigens: Bm86, Bm91 and subolesin. Gene-specific double-stranded (dsRNA) was injected into two tick stages, freshly molted unfed and engorged females, and specific gene silencing was confirmed by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 45 publications
(31 reference statements)
6
90
0
3
Order By: Relevance
“…Similar degrees of silencing have been reported previously in R. microplus (Nijhof et al, 2007). Further, real-time PCR studies and data analysis revealed that significant non-specific silencing took place between As51 and AsC: injection of AsC dsRNA, in Group D, not only significantly reduced the normalized levels of AsC, but also resulted in a significant reduction of As51 (Table 3).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar degrees of silencing have been reported previously in R. microplus (Nijhof et al, 2007). Further, real-time PCR studies and data analysis revealed that significant non-specific silencing took place between As51 and AsC: injection of AsC dsRNA, in Group D, not only significantly reduced the normalized levels of AsC, but also resulted in a significant reduction of As51 (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…Injection of R. microplus females with dsRNA was performed as previously described in Nijhof et al (2007). Freshly molted female ticks were injected with 0.5 μl dsRNA solution…”
Section: Injection Of Ticks With Dsrna and Phenotype Analysismentioning
confidence: 99%
“…RNAi gene silencing was carried out according to previously published methods (Nijhof et al, 2007;Decrem et al, 2008;Hatta et al, 2007). Using the cloned AamOatp plasmid DNA as template and PCR primers (forward, 5ЈTAA TAC GAC TCA CTA TAG GGG GAC CCG GCA AGC ACT TGC TAG TT3Ј; reverse, 5ЈTAA TAC GAC TCA CTA TAG GGT GTT CTT GGA GAC CGC GTC CTC C3Ј) with added T7 promoter sequence (in bold), were used to amplify the template for AamOatp double-stranded RNA (dsRNA).…”
Section: Rna Interference (Rnai) Gene Silencingmentioning
confidence: 99%
“…Suppression can be persistent and act transstadially. For example, injection of double-stranded RNA into engorged R. (Boophilus) microplus females led to the downregulation of mRNA levels in eggs and subsequently in hatched larvae for several weeks [25]. RNAi has been used to study gene function and the role of tick genes in pathogen transmission, and as a screening tool for the identification of potential tick antigens for vaccine development [26,27].…”
Section: Manipulating Gene Expressionmentioning
confidence: 99%